Study of comparative efficacy of Helmintal Mini syrup (toltrazuril, moxidectin) and follow-on drugs against intestinal parasitoses of animals - G. B. Arisova (Российский паразитологический журнал, 2021)
The purpose of the research is comparative assessment of the efficacy and determining the optimal dosage of Helmintal Mini syrup against intestinal parasitoses of animals.Materials and methods. The studies were performed at the premises of the Lvenok veterinary clinic (Moscow). In total, the experiments involved 68 dogs and cats of various breeds, aged 2 to 11 months, infected with intestinal nematodes and coccidia. The animals were divided into test and control groups; the study drug was administered to the test, and the reference drugs were administered to the control. A drug with a toltrazuril content of 50 mg/ml and a drug with a moxidectin content of 0.6 mg/ml were used as follow-on drugs. The diagnosis and therapeutic efficacy of the drugs were confirmed based on the clinical pattern and laboratory tests by absence/presence of protozoan oocysts and helminth eggs in animal feces in laboratory studies (Fülleborn’s method); and we recorded the dynamics of clinical signs of the diseases.Results and discussion. In a comparative assessment of the efficacy of Helmintal Mini syrup with follow-on drugs, it showed the same high efficacy at coccidioses and intestinal nematodoses of animals as registered drugs containing similar active substances. The most effective and safe doses of Helmintal Mini syrup have been determined, namely, 0.5 and 1.0 ml per 1 kg of body weight.